Reliability assessment of transmission line fault clearing system using life data analysis and reliability block diagram - Ridwan M.I.; Yunus B.; Musa A.; Yen K.L. (2023)
The integrity of high voltage transmission lines is extremely important to ensure the continuous electricity supply throughout the country. Faults, such as lightning strikes and flora and fauna encroachments to the transmission lines may cause disruption of electricity supply which will affect the overall power system and lead to a wide scale blackout. Therefore, fault clearing system is deployed to minimize the impact of the faults to the power system by disconnecting and isolating the affected transmission lines specifically. One of the main components of fault clearing system are the protective relays, which are vital in providing the decision making element for correct protection and fault clearing operations. As the electric utility company in Malaysia, Tenaga Nasional Berhad (TNB) is obliged to assess the reliability of the protective relays considering its importance to the fault clearing system. In this paper, a statistical method called Life Data Analysis using Weibull Distribution is applied to assess the reliability of the protective relays. Furthermore, the fault clearing system is modeled using Reliability Block Diagram to simulate the availability of the system and derive reliability indices which will assist TNB in managing the fault clearing system. 2012 IEEE.